An Examination of the Influence of Blue Economy Digital Technology on the Economic Advancement of Fishermen in Batam - Adi, Roni; Aritonang, Mhd Adi Setiawan; Bahri, M. Irvanni; Aswirawan, Maria Yosefina Meinadia Sekar Kinanti; Putri, Rumanintya Lisaria (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to investigate the tangible impact of digital technology on improving the livelihoods and income of fishermen in Batam, in alignment with the principles of a sustainable blue economy. Research Methodology: The research employed a quantitative and qualitative approach through direct field surveys conducted with 52 local fishermen in Batam. The data collected focused on digital tool usage, income changes, and perceived benefits and challenges. Results: Findings reveal that digital technologies—such as meteorological forecasting applications and online marketing platforms—serve as crucial drivers for economic transformation. Approximately 80% of the observed income increases are attributable to digital literacy and technology use. Notably, over 50% of respondents reported a direct rise in income after adopting digital marketing strategies. Conclusion: Digitalization significantly boosts fishermen’s income and economic resilience. However, this transition is impeded by limited technological adaptation among older generations and inadequate internet infrastructure in coastal regions. Limitations: The study is limited by its sample size and geographic scope, focusing solely on fishermen in Batam, which may limit the generalizability of the results to other archipelagic regions. Contribution: This research offers critical insights for policymakers by highlighting the importance of accessible technology training and robust internet infrastructure. These are key to ensuring equitable digital transformation and enhancing the global competitiveness of local fishing communities in Batam.